Long‐term all‐cause and cause‐specific mortality for four bariatric surgery procedures. Issue 2 (25th January 2023) - Adams, Ted D.; Meeks, Huong; Fraser, Alison; Davidson, Lance E.; Holmen, John; Newman, Michael; Ibele, Anna R.; Richards, Nathan; Hunt, Steven C.; Kim, Jaewhan
Abstract: Objective: This retrospective study incorporated long‐term mortality results after different bariatric surgery procedures and for multiple age at surgery groups. Methods: Participants with bariatric surgery (surgery) and without (non‐surgery) were matched (1:1) for age, sex, BMI, and surgery date with a driver license application/renewal date. Mortality rates were compared by Cox regression, stratified by sex, surgery type, and age at surgery. Results: Participants included 21, 837 matched surgery and non‐surgery pairs. Follow‐up was up to 40 years (mean [SD], 13.2 [9.5] years). All‐cause mortality was 16% lower in surgery compared with non‐surgery groups (hazard ratio, 0.84; 95% CI: 0.79‐0.90; p  < 0.001). Significantly lower mortality after bariatric surgery was observed for both females and males. Mortality after surgery versus non‐surgery decreased significantly by 29%, 43%, and 72% for cardiovascular disease, cancer, and diabetes, respectively. The hazard ratio for suicide was 2.4 times higher in surgery compared with non‐surgery participants (95% CI: 1.57‐3.68; p  < 0.001), primarily in participants with ages at surgery between 18 and 34 years. Conclusions: Reduced all‐cause mortality was durable for multiple decades, for multiple bariatric surgical procedures, for females and males, and for greater than age 34 years at surgery. Rate of death from suicide was significantly higher in surgery versus non‐surgery participants only in the youngest age at surgery participants.